Anti-epidermal growth factor receptor-targeted therapy in upper gastrointestinal tract cancers: a meta-analysis. (April 2015) - Li, Ailin; Huang, Xuanzhang; Song, Yongxi; Chen, Xiaowan; Sun, Jingxu; Xu, Huimian; Wang, Zhenning
Abstract This meta-analysis evaluated the efficacy and safety of anti-epidermal growth factor receptor (EGFR) treatment of patients with upper gastrointestinal (GI) tract cancers. A systematic search of multiple databases identified seven randomized controlled trials. Anti-EGFR combination therapy improved disease control rate (DCR) in all patients and progression-free survival (PFS) in patients receiving the same dose of standard therapy as patients receiving standard therapy alone. Combinations of anti-EGFR with non-capecitabine chemotherapy further improved DCR, whereas combinations with capecitabine masked the benefits of DCR and worsened PFS. Overall survival was apparently lower in patients without metastasis, and PFS was apparently improved in patients with squamous cell carcinoma of the esophagus and esophagogastric junction. Anti-EGFR treatment was associated with higher rates of cardiac events, hand–foot syndrome, rash, hypomagnesemia, diarrhea and mucositis and lower rates of neutropenia. Combinations of anti-EGFR agents with non-capecitabine chemotherapy or better supportive care may benefit patients with upper GI tract cancers.